Responsabilidade social empresarial como instrumento de efetivação dos direitos humanos - Simões, Jamili (2021)
The dissertation sought to analyze the themes of human rights and company, under the bias of corporate social responsibility as an instrument of human rights today. For a better understanding of the theme, initially the concept of human rights and the elements that make up this specific branch of law are presented, in addition to the Universal Declaration of Human Rights, a historical landmark on the promulgation of fundamental rights to any human being; the application of human rights in companies, from their conception through the Global Compact, to the creation made by John Ruggie, of the United Nations Guiding Principles on Business and Human Rights; differentiation of concepts, understand: human rights and fundamental rights, corporate social responsibility and social function of the company; understanding of corporate or corporate social responsibility and sustainability. The present study ends with a practical analysis of corporate social responsibility in the national scenario, thus observing the possibility of its application, as well as the instruments that enable its application, provided it is adhered to by companies, whether they are small, medium, large or transnational. Given this approach, the work seeks to answer the following problem: the possibility of human rights in companies; the possibility that corporate social responsibility be an instrument of human rights; the possibility of applying a promotional sanction dor for Social Responsibility; and how Brazil, today, deals with the theme of corporate social responsibility. The subjects are divided into three chapters, based on national and foreign doctrinal teachings, in the legislation related to the theme, as well as guidelines based on international standards (ISOs), and partner programs with the United Nations Organization aiming at sustainability in companies. Thus, the hypothetical-deductive method was used, and as a method of procedure they will be quantitative, bibliographic, doctrinal and documentary. The dissertation is directed to the area of Justice, Company and Sustainability, as well as the research line Company, Sustainability and Functionalization of Law.